Attentional asymmetries – cause or consequence of human right handedness? - Buckingham, Gavin; Carey, David P. (Frontiers in Psychology, 2015)
It is well established that the vast majority of the population favours their right hand when performing complex manual tasks. However, the developmental and evolutionary underpinnings of human manual asymmetries remain contentious. One often-overlooked suggestion is that right handedness may stem from an asymmetrical bias in attention, with the right hand being allocated more attentional resources during bimanual tasks than the left hand (Peters, 1981). This review examines the evidence for attentional asymmetries during a variety of bimanual tasks, and critically evaluates the explanatory power of this hypothesis for explaining the depth and breadth of individual- and population-level manual asymmetries. We conclude that, while the attentional bias hypothesis is well-supported in adults, it requires further validation from a developmental perspective to explain the full breadth of adult manual laterality.